Оцінка здійснення митних процедур в міжнародних рейтингах - Прус, Л. Р.; Prus, Ludmila (КНТУ, 2014)
У статті розглянуто аспекти оцінки та методологія її визначення щодо здійснення митних процедур в країні, систематизовано показники оцінки митної сфери, визначено взаємозв’язок між міжнародними індексами в контексті митних процедур. The article defines and analyzes the methodological principles of evaluation customs procedures in the countries. Done systematization of international indexes that include indicators for assessing the customs sphere, defined the relationship between them in the context of customs procedures and a retrospective analysis of Customs Procedures in Ukraine. Established that customs procedures are investigated to determine the Global Competitiveness Index, Logistics Performance Index, processing report «Doing Business», Index off Trade Facilitation and customs procedures for evaluation using the Customs Code.
Evaluation customs procedures international ratings
Keywords: митні процедури; міжнародні індекси; бенчмаркінг; показник; оцінка; customs procedures; international indices; benchmarking; index score